Memes and millennial voters: Identities of an indonesian female political leader - Gesang M. N. Putra, Nurul Fitri Hapsari, (Opción, 2019)
This research aimed to reveal how the identity of Khofifah as the East Java Governor candidacy was redefined through memes shared by millennials in social media during the East Java governor election campaign from February – Juli 2018. After analyzing with Kress Van Luween’s multimodality approach and Kevin Robin’s identity theory, memes selected with purposive sampling technique indicated the intersection of religious, traditional, and national identities of Khofifah signified with several pop-cultural symbols. In conclusion, the intersecting identities of Khofifah popular among millennials seems to adopt the political style of Sengkuni, an antagonist character in Javanese culture.